Clinical characteristics and etiology of children with bronchiolitis before and during the COVID-19 pandemic in Suzhou, China - Jiang, Xiaohui; Wang, Ting; Dai, Ge; Sun, Huiming; Jiang, Wujun; Chen, Zhengrong; Yan, Yongdong (Frontiers in Pediatrics, 2022)
Objective: We sought to compare the clinical characteristics and etiology of children with bronchiolitis in Suzhou before the pandemic of coronavirus disease 2019 (COVID-19) with those during the pandemic. Methods: Children who were hospitalized with bronchiolitis in the Department of Respiratory Disease, Children’s Hospital of Soochow University were retrospectively enrolled over 3 consecutive years (2019, 2020, and 2021) from February 1 to January 31. Medical records were reviewed for etiology, clinical manifestations, and laboratory examination results. Results: The pathogen detection rate and the positive respiratory syncytial virus (RSV) detection rate were lowest in 2020 and highest in 2021. The rate of human rhinovirus detection in 2021 was higher than that in 2019 but similar to that in 2020. The RSV-positive rate differences among the 3 years varied by age group. Regarding the monthly distribution of RSV-positive cases over the 3-year study, all age groups showed a significant increase in the number of cases during the winter of 2021, and this increase started as early as October. With regard to clinical manifestations, the proportion of children presenting with stuffy nose rhinorrhea in 2021 [73.33% (165/225)] was greater than that in 2019 [48.61% (122/251)] and 2020 [57.06% (97/170)], while the proportion of children with gastrointestinal symptoms in 2021 [11.56% (26/225)] was smaller than that in 2019 [25.50% (64/251)] but similar to that in 2020 [17.06% (29/170)]. Conclusions: After the implementation of COVID-19 pandemic-related interventions, significantly lower pathogen detection and RSV-positive rates were observed in children with bronchiolitis in 2020. An upward trend in these rates was observed in 2021, coinciding with the relaxation of COVID-19 prevention measures. Strengthening infection control and surveillance systems is extremely important for future work.